Childcare Providers' Nominations of Preschool Children at Risk for Mental Health Problems: Does it Discriminate Well Compared to the Caregiver-Teacher Report Form (C-TRF)?. Issue 3 (16th April 2022) - Stensen, Kenneth; Lydersen, Stian; Stenseng, Frode; Wallander, Jan Lance; Tveit, Håvard; Drugli, May Britt
ABSTRACT: Childcare providers are vanguards in identifying children at risk for mental health problems. Thus, the aim of the current study was to investigate the accuracy of childcare providers' nominations of children at risk for mental health problems against a well-established comparator, the Caregiver-Teacher Report Form. Findings from the present study, including 1430 children aged one to six years old and 169 childcare providers from 57 childcare centers, indicates that nominations in the form of concerns should be taken seriously and followed up with additional screening or assessment and consideration for referral. However, nominations also created a considerable portion of false positives. These results suggest that when childcare providers become concerned about a child, it may be beneficial to apply a psychometrically sound screening instrument to decrease the rate of false positive nominations. This may help childcare providers to act more promptly by confirming or discarding their initial concerns.